(untitled) (Journal of Naval Architecture and Marine Engineering, 2019)
The objective of the current paper is to study the flow around Seiun Maru Highly Skewed (HSP) marine propeller by assessment of blade forces and moments under non-cavitating case. The calculations are performed in open water (steady case) and non-uniform ship wake (Unsteady case). The governing equations based on Reynolds Averaged Navier-Stokes Equation (RANSE) are solved using Finite Volume Method. Ansys Fluent 14.0 is used to implement the simulation. For the steady case, Moving Reference Frame (MRF) is selected while sliding mesh technique is adopted for the unsteady case. Calculated open water performances in terms of thrust and torque coefficients fit very well with experimental data for a wide range of advance ratio. In the unsteady calculations, axial velocities, deduced from the nominal wake, are introduced in the Ansys fluent code. To locate suitably the non-uniform wake in the propeller front plane, three positions of inlet wake have been taken into account to determine their effects on the accuracy of the results. Obtained results show that computed performances are improved compared to panel method when the inlet is close to the propeller.